Developmental disabilities in Africa: a scientometric review - Lim, Mengyu (2023)
Background: Developmental disabilities are disproportionately more investigated in higher-income countries. However, global prevalence of developmental disabilities indicate that a large proportion of individuals with disabilities reside in low- and middle-income nations. Aims: The present work therefore aims to conduct a scientometric review to survey available literature on developmental disabilities in low- and middle-income countries belonging to the continent of Africa. Methods and procedures: A literature search was conducted on Scopus, where a total of 1720 relevant publications (and an accompanying 66 thousand references) were found, representing research conducted between 1950 to 2022. Then, document co-citation analysis was performed to chart significant co-citation relationships between relevant articles and their cited references. Outcomes and results: The generated network based on document co-citation analysis revealed a total of 14 distinct thematic research clusters and 12 significant documents that have been frequently cited in the literature on developmental disabilities in Africa. Conclusions and implications: The scientometric review revealed a trend of broadening research towards systems of care, away from a medical model of disease. It is projected that future research will continue to capitalise on inter-disciplinary strengths to arrive at a more nuanced understanding of developmental disability from all levels – individuals, families, to communities.